CRYPTOGENIC INCREASED ACTIVITY OF ASPARTATE AMINOTRANSFERASE: A CASE REPORT - Tjaša Žagar; Rok Orel (The Society for Children with Metabolic Disorders, 2021)
We present a case of cryptogenic elevation of aspartate aminotransferase (AST) activity. AST is an enzyme found in many tissues, so the serum activity of this enzyme may be elevated in various diseases. If there is an isolated increase in AST, we are therefore faced with a diagnostic challenge and many diseases must be ruled out. When most diseases have been ruled out with a high probability, it is referred to as a cryptogenic increase in AST activity. Some studies have shown that part of this increase can be explained by macroenzymes, more speciﬁcally by macro - AST. In the case presented, we also suspected that the increased AST activity was due to macro - AST. As the determination of macro - AST is not possible in the laboratory of the University Clinical Centre Ljubljana, it has not been possible to conﬁrm or refute the diagnosis.